Burnout among English language teachers in Malaysia - Mukundan, Jayakaran; Khandehroo, Koroush (Clute Institute for Academic Research, 2010)
The phenomenon of burnout has always been under scrutiny, especially with reference to the teachers and their demographics. This study has deliberately focused on the English teachers’ burnout and its relation with their demographics of age and workload in Malaysia. The findings showed that burnout is evident at high levels in all dimensions. In addition, some age and workload categories demonstrated significant relations with emotional exhaustion, depersonalization and reduced personal accomplishment. The findings would help school administrators consider such factors as important in the effectiveness of English teachers.